HP04: Absence of cardiac parasympathetic dysfunctions in elderly migraine?. (March 2022) - Chouchou, F.; Créach, C.; Pichot, V.; Celle, S.; Hupin, D.; Barthélémy, J.C.; Peyron, R.; Roche, F.
Abstract : Background: Cardiac vagal dysfunction was documented in middle-aged patients with migraine. However, vagal activity depends on several psychophysical or physiological factors such as anxiety, depression, lifestyle or age. In this work, we studied cardiac parasympathetic activity in elderly volunteers with past or current migraine. Methods: Among PROOF-SYNAPSE study, 28 (74.6±1.0 years) and 19 (74.3±1.1 years) out of these normal subjects were divided in two groups having a history of past migraine (PM) and still having current episodic migraine (CM), respectively. Twenty-three healthy control (HC) subjects without any history of headache nor chronic pain were matched on gender and age (74.6±1.0 years). These subjects underwent clinical examination including questionnaires about depression and anxiety (Hospital Anxiety and Depression Scale), cardiorespiratory testing (VO2 max), daily energy expenditure (Population Physical Activity Questionnaire), and 24 h ECG Holter monitoring. Diurnal and nocturnal temporal and frequential interval RR (RR) variability analyses were applied. Results: Neither temporal nor spectral analyses of RR variability showed differences between CM, PM, and HC groups. CM patients reported more anxiety (p<0.05) and depression (p<0.05), without any different in daily energy expenditure and maximum oxygen consumption. In CM group, anxiety and daily energy expenditure were correlated with diurnal overall autonomic regulation activity (spectral total power, t=-2.27, p=0.043, t=2.30, p=0.041, respectively) in multiple correlational analysis. Conclusion: In an elderly population, migraine does not seem to be directly associated with cardiac parasympathetic dysfunctions. However, sedentary lifestyle and anxiety in chronic diseases could contribute to the autonomic cardiac dysfunctions in some patients with migraine.